Analyze and evaluate the state of art scheme for fault tolerant WSN - Kaur, Taranpreet (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
Wireless Sensor Network (WSN) offers a medium that can transmitted signals, microwave, satellite or radio signals for communication process. Wireless Sensors acts as a transceiver that is it receive the signal as well as transmit the signal to the destination. WSN includes a group of nodes that are typically low in functionality. Wi-Fi tools, in addition to optical computing, expanded the major event correlated with detector nodes, the new developments in micro-electro - mechanical systems development. It results in realistic viability for the specific prospect of flowering associated with WSNs. The WSN network faces two types of failures in the networks namely the physical fault and the network fault. When it comes to the physical fault, the process is termed as fault detection and when it is associated on the base of data level. Some schemes are comparable to a common social network, but typically depend on different personality stereotypes that each single PC relates to one individual character. Such problems usually occur when a reputational context is fooled through a disproportionately high effect on a confidence attacking PC.